Unpacking school culture as a multidimensional construct: Validation of the School Culture Scale (SCS) in educational leadership contexts (Research, Society and Development, 2026)
Understanding and measuring school culture remains a critical yet methodologically challenging task in educational research, given its multidimensional and context-dependent nature. This study contributes to this field by providing a comprehensive psychometric validation of the School Culture Scale (SCS) within the Greek educational context, while also addressing broader issues related to the cross-cultural applicability of measurement instruments. Drawing on data from school principals, the study employs both Exploratory Factor Analysis (EFA) and Confirmatory Factor Analysis (CFA) to examine the scale’s internal structure, alongside reliability and correlational analyses. The findings demonstrate strong internal consistency across all dimensions and provide empirical support for the original four-factor model, confirming the theoretical robustness of the instrument. At the same time, minor διαφοροποιήσεις in item loadings highlight the sensitivity of school culture constructs to contextual and institutional conditions. The positive intercorrelations among factors further reinforce the conceptualization of school culture as a dynamic and interconnected system shaping relationships, expectations, and learning processes within schools. Beyond its national scope, the study offers important contributions to the international literature by supporting the cross-cultural validity of the SCS while emphasizing the necessity of context-sensitive validation. The results position the SCS as a robust and adaptable tool for comparative research, as well as for informing leadership practices and school improvement efforts. Overall, the study advances both the methodological rigor and the theoretical understanding of school culture as a key driver of educational quality and organizational change.